In vitro regeneration of stevia (stevia rebaudiana bertoni) and evaluation of the impacts of growth media nutrients on the biosynthesis of steviol glycosides (SGs) - Ghose, Asish Kumar; Abdullah, Siti Nor Akmar; Md Hatta, Muhammad Asyraf; Megat Wahab, Puteri Edaroyati (MDPI AG, 2022)
A plant tissue culture protocol from stevia was optimized for the production of planting materials and the natural sweetener, rebaudioside A. The highest survivability (88.90% ± 5.55) of explants was achieved at 15 and 30 days after culture initiation (DACI) on Murashige and Skoog (MS) media by sterilization with 30% Clorox (5 min) and 10% Clorox (10 min), respectively. Supplementation of MS with 0.50 mg/L 2,4-Dichlorophenoxyacetic acid (2,4-D) and 0.10 mg/L zeatin produced 50% callus at 15 DACI while 1.50 mg/L 2,4-D and 0.10 mg/L zeatin at 30 DACI increased callus production to 76.67%. The highest shoot proliferation per callus was achieved with 10.00 mg/L 6-benzyl amino purine (BAP) in MS at 15 DACI (5.80) and 30 DACI (12.33). The longest shoots of 4.31 cm and 6.04 cm at 15 and 30 DACI, respectively, were produced using BAP (10.00 mg/L) and 1.00 mg/L naphthalene acetic acid (NAA). MS media (0.50 strength) induced 2.86 and 6.20 roots per shoot and produced 3.25 cm and 7.82 cm long roots at 15 and 30 DACI, respectively. Stevia grown on 0.25 MS accumulated the highest concentration of rebaudioside A (6.53%), which correlated with the expression level of its biosynthetic gene uridine-diphosphate-dependent (UDP)-glycosyltransferase (UGT76G1).